'Frexting': exploring homosociality among girls who share intimate images. (28th May 2022) - Setty, Emily
ABSTRACT: This paper presents an examination of 'frexting' ('friend' + 'sexting'), which is defined as the exchange of personally-produced intimate images among friends. It draws upon accounts of frexting shared by teenage girls during a 2016 study investigating sexting conducted in Surrey, England. Frexting is theorised as a form of homosociality among girls and explores the extent to which and how it reflects, reproduces and subverts the dominant gendered social order within youth digital intimacies. The analysis suggests that while frexting involves intimate self-representation away from the male gaze, it reflects and reinforces a post-feminist cultural landscape characterised by (self-)scrutiny and regulation of girls' bodies and bodily self-representations. Frexting worked to demonstrate an authentic, relaxed, carefree and confident but, importantly, non-sexual sensibility, with implications for who and what constitutes legible participation. While subverting normative interpretations of girls' bodies as inherently, and problematically, sexual, frexting did not fundamentally trouble the post-feminist cultural landscape within which the girls were operating. The paper concludes by arguing that for frexting to become a truly emancipatory endeavour, it is necessary to dismantle the socio-cultural context that restricts and regulates girls' abilities to relate to and represent their bodies.